Translation-dependent and -independent mRNA decay occur through mutually exclusive pathways defined by ribosome density during T cell activation - Mercier, Blandine C.; Labaronne, Emmanuel; Cluet, David; Guiguettaz, Laura; Fontrodona, Nicolas; Bicknell, Alicia; Corbin, Antoine; Wencker, Mélanie; Aube, Fabien; Modolo, Laurent; Jouravleva, Karina; Auboeuf, Didier; et al.

(untitled) (Genome Research, 2024)
mRNA translation and decay are tightly interconnected processes both in the context of mRNA quality-control pathways and for the degradation of functional mRNAs. Cotranslational mRNA degradation through codon usage, ribosome collisions, and the recruitment of specific proteins to ribosomes is an important determinant of mRNA turnover. However, the extent to which translation-dependent mRNA decay (TDD) and translation-independent mRNA decay (TID) pathways participate in the degradation of mRNAs has not been studied yet. Here we describe a comprehensive analysis of basal and signal-induced TDD and TID in mouse primary CD4+ T cells. Our results indicate that most cellular transcripts are decayed to some extent in a translation-dependent manner. Our analysis further identifies the length of untranslated regions, the density of ribosomes, and GC3 content as important determinants of TDD magnitude. Consistently, all transcripts that undergo changes in ribosome density within their coding sequence upon T cell activation display a corresponding change in their TDD level. Moreover, we reveal a dynamic modulation in the relationship between GC3 content and TDD upon T cell activation, with a reversal in the impact of GC3- and AU3-rich codons. Altogether, our data show a strong and dynamic interconnection between mRNA translation and decay in mammalian primary cells.